Increased Growth Differentiation Factor 15 Levels Are Associated with HIV-Associated Neurocognitive Impairment: A Pilot Study - Ali Boustani; Mary K. Ford; Jacqueline R. Kulbe; Anna E. Laird; Leeann Shu; Matthew Spencer; Bryant Avalos; Kyle C. Walter; Ronald J. Ellis; Jerel Adam Fields (Brain Sciences)
Background/Objectives: HIV-associated neurocognitive impairment (NCI) remains a prevalent issue among people with HIV (PWH) despite advancements in antiretroviral therapy (ART). The pathogenesis of HIV-associated NCI is linked to chronic neuroinflammation caused by HIV, even in those with successful viral suppression. Growth Differentiation Factor 15 (GDF15), a protein involved in inflammatory and metabolic stress responses, has emerged as a key player and potential biomarker for various neurological conditions. This study investigates the relationship between GDF15 expression and HIV-associated NCI. Methods: PWH from the California NeuroAIDS Tissue Network (CNTN) underwent comprehensive neuropsychological exams within 12 months before death and were categorized based on cognitive performance. We examined GDF15 levels in their CSF (Cerebrospinal Fluid) and brain tissues using immunoblotting, immunohistochemistry, double immunolabeling, and ELISA. Results: The cohort was of a similar age across HIV-associated NCI statuses (mean = 40.5), with a predominance of males (77%). The mean plasma viral load was 3.56 log10 copies/mL for Neurocognitively Unimpaired (NUI) PWH and 5.38 log10 copies/mL for people with HIV-associated NCI. GDF15 protein levels were significantly elevated in the frontal cortices of PWH with NCI compared to NUI PWH. Conclusions: The findings indicate that GDF15 may play a role in the pathogenesis of HIV-associated NCI, possibly through neuroinflammatory mechanisms. The strong association between GDF15 levels and cognitive impairment severity suggests its potential as a biomarker for the early detection and monitoring of NCI in PWH.